2012
DOI: 10.1051/0004-6361/201219669
|View full text |Cite
|
Sign up to set email alerts
|

The size-luminosity relation atz = 7 in CANDELS and its implication on reionization

Abstract: Context. The exploration of the relation between galaxy sizes and other physical parameters (luminosity, mass, star formation rate) has provided important clues for understanding galaxy formation, but such exploration has until recently been limited to intermediate redshift objects. Aims. We use the currently available CANDELS Deep+Wide surveys in the GOODS-South, UDS and EGS fields, complemented by data from the HUDF09 program, to address the relation between size and luminosity at z ∼ 7. Methods. The six dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
157
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(190 citation statements)
references
References 84 publications
31
157
2
Order By: Relevance
“…However, both the mass-size and the luminosity-size relations at high redshift are found to be very shallow following r M found by Huang et al (2013). These measurements are completely consistent with the surprisingly constant size scaling for late type galaxies at all redshifts z 0 3 = -seen in the CANDELS data set (r M e 0.22 µ ; see van der Wel et al 2014) and there is no convincing evidence for a change in these scaling relations at higher redshifts (but see Grazian et al 2012). This suggests that a galaxy magnified by a factor 10 m = is intrinsically only 1.7´smaller than a non-lensed galaxy observed in the field.…”
Section: Assumptions About the Galaxy Size Distributionsupporting
confidence: 73%
“…However, both the mass-size and the luminosity-size relations at high redshift are found to be very shallow following r M found by Huang et al (2013). These measurements are completely consistent with the surprisingly constant size scaling for late type galaxies at all redshifts z 0 3 = -seen in the CANDELS data set (r M e 0.22 µ ; see van der Wel et al 2014) and there is no convincing evidence for a change in these scaling relations at higher redshifts (but see Grazian et al 2012). This suggests that a galaxy magnified by a factor 10 m = is intrinsically only 1.7´smaller than a non-lensed galaxy observed in the field.…”
Section: Assumptions About the Galaxy Size Distributionsupporting
confidence: 73%
“…As for galaxy sizes, we adopt a lognormal distribution with a mean half-light radius of 0 15 and sigma = 0 07. For consistency with previous results (Bouwens et al 2004;Ferguson et al 2004;Hathi et al 2008;Oesch et al 2010Oesch et al , 2014Grazian et al 2011Grazian et al , 2012Huang et al 2013), the distribution is based on the sizes derived from spectroscopically confirmed LBG samples at z ∼ 4 (Vanzella et al 2009), while accounting for a redshift evolution of the intrinsic physical size of galaxies with a factor of (1 + z) −1 . HST observations of dropout galaxies at z > 6 redshifts also reveal small sizes of less than 0 3 (Mosleh et al 2012;Ono et al 2013), and smaller for galaxies fainter than M UV − 21 mag.…”
Section: Completeness Simulationssupporting
confidence: 59%
“…Half-light radius measured using elliptical apertures in the rest-frame UV image as a function of the absolute rest-frame UV magnitude. LARS measurements from this work (red diamonds) are shown together with the literature estimations by Overzier et al (2010) corresponding to the median value of their z < 0.3 LBAs, observed in the near-infrared bands, by Jiang et al (2013) for a sample of z ∼ 5.7, 6.5, 7.0 LAEs (cyan dots), by Bond et al (2012) for the stack and subsamples of LAEs at z 2−3 (black circles, magenta squares), by Grazian et al (2012) which measured SExtractor half-light radii for a sample of z-drop outs (green triangles), and by Ono et al (2013) for a sample of high signal-to-noise zand Y-drop outs detected in Hubble Ultra Deep Field, UDF12 (black stars).…”
Section: Lars Galaxies As Seen At Z ∼mentioning
confidence: 83%
“…These include, -Continuum-selected Lyman break galaxies (LBGs) at z ∼ 3, with and without Lyα in emission (Pentericci et al 2010); at z ∼ 1, 2, and 3 (Mosleh et al 2011), at 1.5 < z < 3.6 (Law et al 2012); at z ∼ 1.8 (Lotz et al 2004); z-drop outs at z ∼ 7 (Grazian et al 2012); high signal-to-noise z-and Y-drop outs detected in the Hubble Ultra Deep Field, UDF12 (Ono et al 2013). -Compact star-forming galaxies (cSFGs) at 2 < z < 3 (Barro et al 2013).…”
Section: Lars Galaxies At Z ∼mentioning
confidence: 99%